Обучение иностранных студентов как аспект интернационализации образования - Захаренко, Т. А.; Zakharenko, T. A. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Internalization of higher education is an important element of globalization. Academic mobility is a priority for the synchronization of educational programs of different countries. The author considers some aspects of the training of foreign students.
Training of foreign students as aspect of internationalization of education
Т.А.Захаренко, ст. препод.УО «Белорусская государственная сельскохозяйственная академия» (Беларусь, Могилевская область, г. Горки)
Keywords: globalization; international education; foreign students; adaptation